The Sensitivity of Firms’ Investment to Uncertainty and Cash Flow: Evidence From Listed State-Owned Enterprises and Non-State-Owned Enterprises in China - Muhammad Arif Khan; Xuezhi Qin; Khalil Jebran; Abdul Rashid (SAGE Open, 2020)
This study examines the association between various uncertainties and corporate investment and further investigates this association between state-owned enterprises (SOEs) and non-state-owned enterprises (non-SOEs). Moreover, this study analyzes the indirect effects of uncertainty on corporate investment through cash flow. The current research uses an unbalanced panel data of Chinese nonfinancial listed firms for the period 1999–2016. To control endogeneity issues, this study applies a robust two-step system generalized method of moments (GMM) technique to estimate the model. Empirical findings indicate that market-based and firm-specific uncertainties have positive effects, whereas economic policy and CAPM-based uncertainties have negative effects on corporate investment. Furthermore, results indicate that the effects of market-based, CAPM-based, and firm-specific uncertainties (economic policy uncertainty) were less (more) prominent for SOEs. Additional analyses show that cash flow stimulates the effect of firm-specific uncertainty on SOEs’ investment, whereas it weakens the influence of CAPM-based uncertainty (economic policy uncertainty) on investment of non-SOEs (SOEs). Moreover, cash flow attenuates the market uncertainty effect on investment.